Influencia de la relación extracto de nabo (Brassica rapa) / ácido Tungsteno fosfórico para incrementar la producción de energía en bioceldas de almidón - López Jara, Luis Alberto (2017)
The relationship between turnip extract / phosphoric tungsten acid, in the presence of hydrogen peroxide and using potato starch as substrate, was investigated. For this, tests were performed varying the concentration of turnip extract, hydrogen peroxide and also tests in the absence thereof. The voltages of the bioceldas are measured in millivolts (mV) by means of a digital multimeter. The influence of mildew was analyzed, concluding that from the appearance of this, the voltage increases. The highest voltages obtained are 364-374 mV, when the ratio of turnip extract / phosphoric tungsten acid is in a range of 0-130, in the presence of hydrogen peroxide. The concentration of hydrogen peroxide varies according to the total volume of the biocells